Implementation of IoT system using block chain with authentication and data protection - Lee, Chan Hyeok; Kim, Ki Hyung (International Conference on Information Networking, 2018)
In a block-chain IoT environment, when data or device authentication information is put on a block chain, personal information may be leaked through the proof-of-work process or address search. In this paper, we apply Zero-Knowledge proof to a smart meter system to prove that a prover without disclosing information such as public key, and we have studied how to enhance anonymity of block chain for privacy protection.
Keywords: Device authentications; Personal information; Privacy protection; Proof of work; Public keys; Security; Smart grid; Zero knowledge proof; Block Chain; IoT; Security; Smart Grid